2011
DOI: 10.1016/j.pneurobio.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin—A pleiotropic, orchestrating regulator molecule

Abstract: Melatonin, the neurohormone of the pineal gland, is also produced by various other tissues and cells. It acts via G protein-coupled receptors expressed in various areas of the central nervous system and in peripheral tissues. Parallel signaling mechanisms lead to cell-specific control and recruitment of downstream factors, including various kinases, transcription factors and ion channels. Additional actions via nuclear receptors and other binding sites are likely. By virtue of high receptor density in the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
757
2
40

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(807 citation statements)
references
References 694 publications
(890 reference statements)
8
757
2
40
Order By: Relevance
“…Melatonin is also involved in several and important functions such as vasomotor control and adrenal function, possesses antiexcitatory actions, regulates immune function and energy metabolism, including anti-inflammatory properties (Hardeland et al 2011). Melatonin is highly lipophilic and consequently study, it has been reported that in vivo oxidative stress production, accompanied by increasing oxidative stress markers after mustard gas exposure, was counteracted by melatonin administration (Pohanka et al 2011).…”
mentioning
confidence: 99%
“…Melatonin is also involved in several and important functions such as vasomotor control and adrenal function, possesses antiexcitatory actions, regulates immune function and energy metabolism, including anti-inflammatory properties (Hardeland et al 2011). Melatonin is highly lipophilic and consequently study, it has been reported that in vivo oxidative stress production, accompanied by increasing oxidative stress markers after mustard gas exposure, was counteracted by melatonin administration (Pohanka et al 2011).…”
mentioning
confidence: 99%
“…Even if the most well known function of melatonin in human beings is its contribution to synchronization of biologic rhythms, with a key role in light-dark cycles, an important body of evidence in recent years has suggested that melatonin may be involved in other functions, including body temperature modulation, antiproliferative effects, antioxidant effects, interrelationship with the immune system, etc. (16)(17)(18)(19)(20)(21)(22), also acting as a "neuroendocrine transducer" of information collected from the environment (23). IGFBP3, may also be influenced by circadian genes.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has pleiotropic eff ects acting at diff erent levels of the human physiology (Hardeland et al 2011). Th erefore, the decreased melatonin production can be related to diff erent pathological situations and requires a specifi c attention.…”
mentioning
confidence: 99%